Turkish Defense Expenditures in View of Ups and Downs in Turkish-Greek Relations: Is There a Reaction? - Gunluk-Senesen, Gulay (Études helléniques / Hellenic Studies, 2001)
This article attempts to find out whether Turkish defense expenditures during 1983-2000 and relations with Greece in the same period have a common pattern. The choice of the period of analysis is based on availability of detailed data on Turkish defense expenditures. Recent empirical literature on a long-run arms race between Turkey and Greece is inconclusive. We find that with some indicators, Turkish defense spending decisions react to a continuum of perceived threats, not attributable at all to those from Greece. The patterns of other indicators of Turkish defense expenditures are far from providing supporting evidence for reactionary responses to whether conflict or harmony prevails in bilateral relations.